Employability skills of higher education graduates: Little consensus on a much-discussed subject - Suleman, F. (2021)
The expansion of higher education (HE) has given rise to research on skills that smooth transition and benefit the careers of graduates. We examine literature that attempts to inform HE institutions and policy makers about the skills required in the labor market. A variety of methods have been implemented to collect data on employability skills. It has been acquired directly using hiring criteria but it has also been gleaned indirectly on the basis of employers' satisfaction with graduates' skills. The evidence shows little consensus on which skills actually foster employability. Wide agreement exists on the need for relational skills, namely interpersonal, communication and teamwork abilities, which are reported in almost all papers. Moreover, the literature suggests that some employers find graduates are poorly prepared for teamwork but they recognize the good level of IT skills. We are concerned about the lack of agreement on the necessary skills as well as the perception that graduates are poorly prepared. Conceptual issues and methodological solutions are likely to have generated results that contain some degree of ambiguity. Researchers and policy makers therefore remain uncertain about graduate skills that match workplace requirements and foster employability.